PERILAKU DIET BERDASARKAN PENGETAHUAN TENTANG INDEKS GLIKEMIK PADA PASIEN DIABETES MELITUS PESERTA SEKOLAH PROLANIS BANGUNJIWO BANTUL - Hidayati, Titiek; Suryani, Lilis; Akrom, Akrom (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Cases of non-communicable diseases such as diabetes are often experienced by people with old age. Even in the Bantul region, this disease is included in the 10 groups of diseases that many people suffer. There needs to be independence from the community so that they do not depend on health service facilities such as the nearest health center. There are health cadres, providing education, carrying out actions with sticky media games, and closing with a temporary blood sugar level check. The method used to test the results of the service that has been carried out is by pre-test and post-test. Based on the test results, there is a significant relationship between knowledge and attitude variables. This can be because respondents who have been exposed to information regarding the glycemic index of food have a positive attitude towards choosing low-glycemic foods. Although there is no good relationship between attitude and behavior. In addition, there was an increase in the number of respondents who answered correctly on the pre-test and post-test on the pre-knowledge variable from 81 people to 96 people, the attitude variable from 85 people to 95 people, and the behavior variable from 80 people to 90 people. In addition, examination of blood sugar levels while on the chart shows that 38% are in the pre-diabetic category and 62% have normal blood sugar levels. The conclusion is that there is a positive increase between knowledge and attitudes after being given interventions in the form of education and checking blood sugar levels.